2015
DOI: 10.1017/cjn.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Risk Factors for Major Recurrence of Intracranial Aneurysms after Coiling

Abstract: Background: Recurrence after intracranial aneurysm coiling is a highly prevalent outcome, yet to be understood. We investigated clinical, radiological and procedural factors associated with major recurrence of coiled intracranial aneurysms. Methods: We retrospectively analyzed prospectively collected coiling data . We recorded characteristics of aneurysms, patients and interventional techniques, pre-discharge and angiographic follow-up occlusion. The Raymond-Roy classification was used; major recurrence was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Ruptured aneurysms, aneurysms with intraluminal thrombus, and incompletely coiled aneurysms are well-documented risk factors for recurrence following coil embolization 10 11. The finding of male gender as an additional risk factor has also been previously reported 9 23…”
Section: Discussionmentioning
confidence: 73%
“…Ruptured aneurysms, aneurysms with intraluminal thrombus, and incompletely coiled aneurysms are well-documented risk factors for recurrence following coil embolization 10 11. The finding of male gender as an additional risk factor has also been previously reported 9 23…”
Section: Discussionmentioning
confidence: 73%
“…41 However, incomplete coiling is not the only factor associated with regrowth as increased total aneurysm size, packing density, older age, male sex, hypertension, and ruptured aneurysm have also been associated with aneurysm regrowth after coiling in retrospective analyses. [42][43][44] The mortality rate seems to be high in patients that received surgical retreatment based on our meta-analysis. Another metaanalysis suggested that mortality may actually be 0% (95% CI = 0.0%-2.5%).…”
Section: Discussionmentioning
confidence: 68%
“…Analysis of a matched (aneurysm location, diameter, and neck size) cohort demonstrated not only an overall higher risk of recanalization in ruptured IA but also shorter period and higher degrees of recanalization and a higher percentage of retreatment when compared with unruptured IA [95]. It is increasingly recognized that the need of retreatment after GDC embolization are more common in ruptured than unruptured IA [20,38,64,71,72].…”
Section: The Fundamental Difference Between Ruptured and Unruptured Iamentioning
confidence: 99%
“…Unruptured IAs tend to have more viable SMCs in their walls, providing unruptured IAs increased opportunity to heal after embolization. This could explain why unruptured IAs have lower rebleeding rates [20,75], necessitate less retreatment [20,31,38,71,72,82], and are more stable after GCD embolization than ruptured IAs [1, 13, 26, 43, 70-72, 78, 95, 101].…”
Section: Intraluminal Thrombosis Destabilizes the Ia Wall And Influenmentioning
confidence: 99%